2005
DOI: 10.1112/s0024609304003698
|View full text |Cite
|
Sign up to set email alerts
|

Transitive and Hypercyclic Operators on Locally Convex Spaces

Abstract: Solutions are provided to several questions concerning topologically transitive and hypercyclic continuous linear operators on Hausdorff locally convex spaces that are not Fréchet spaces. Among others, the following results are presented. (1) There exist transitive operators on the space ϕ of all finite sequences endowed with the finest locally convex topology (it was already known that there is no hypercyclic operator on ϕ). (2) The space of all test functions for distributions, which is also a complete direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…In contrast, by Conejero [16] there do exist strongly continuous semigroups (T (t)) t≥0 on ϕ that are topologically transitive, that is, for any pair of nonempty open subsets U, V of ϕ there exists t ≥ 0 such that T (t)(U ) ∩ V = ∅. The analogous result for operators is due to Bonet, Frerick, Peris and Wengenroth [11].…”
Section: Nonexistence Of Hypercyclic Semigroupsmentioning
confidence: 88%
“…In contrast, by Conejero [16] there do exist strongly continuous semigroups (T (t)) t≥0 on ϕ that are topologically transitive, that is, for any pair of nonempty open subsets U, V of ϕ there exists t ≥ 0 such that T (t)(U ) ∩ V = ∅. The analogous result for operators is due to Bonet, Frerick, Peris and Wengenroth [11].…”
Section: Nonexistence Of Hypercyclic Semigroupsmentioning
confidence: 88%
“…In [32] it was shown that = ⊕ ℓ , 1 ≤ < ∞, and = ⊕ = D(Ω), where is the space of rapidly decreasing functions and D(Ω) is the space of test functions on an open set Ω ⊂ R , support a noninjective hypercyclic operator. Shkarin [33] generalized this result to the present context by showing the existence of hypercyclic operators of the form = + for noninjective.…”
Section: Examplementioning
confidence: 99%
“…It is well known that these notions are equivalent for continuous linear operators on Fréchet spaces by Baire's category theorem (see, for instance, [21,22]). However, there exist examples of continuous linear operators on non-metrizable locally convex spaces that are topologically transitive and not hypercyclic [23]. Moreover, for any non-trivial Banach space X there exists a multivalued linear operator A = {0} × X that is hypercyclic and not topologically transitive (cf.…”
Section: Preliminariesmentioning
confidence: 99%